EFEKTIVITAS KERJA PEGAWAI BIDANG KEPEGAWAIAN PADA BADAN PENELITIAN DAN PENGEMBANGAN DAERAH KOTA PALU - Ramadan, Ramadan (Katalogis, 2019)
This research was conducted with the aim of analyzing the Employee Effectiveness of Staff in the Regional Research and Development Agency of the City of Palu. The theory used as a reference is the theory of Work Effectiveness from Richard M. Steers. The basis of this research is qualitative with descriptive type of research. The techniques used in data collection are field observations, in-depth interviews and documentation. Then the data and interview results obtained were analyzed descriptively qualitatively. Research location in the Regional Research and Development Agency of the City of Palu. Research informants were 5 (five) employees with data sources including primary data and secondary data. The results showed that in looking at the effectiveness of employee performance in the field of staffing at the Regional Research and Development Agency of the City of Palu can be seen from 3 aspects, namely aspects of adaptability, aspects of work performance and aspects of job satisfaction where overall employee performance in the Employment Agency and Regional Development of Palu City has been effective. From the aspect of adaptability, employees have been able to adjust themselves, able to create communication and be able to create good cooperation. From the aspect of work performance employees have also been effective, where employees have been able to carry out their duties skillfully, with good skills, and discipline in completing tasks, employees are also supported by the ability to operate computers well, have a good personality and are responsible. Whereas when viewed from the aspect of employee job satisfaction it can also be said to be effective, where employees have felt fair in assessing and giving their work by the leadership, feeling comfortable with the work environment, and employees also feeling that they have had the opportunity to advance and improve.